Artificial Intelligence and Islamic Jurisprudence: A Critical Analysis of Legal and Ethical Challenges in Automated Decision-Making - Kamran Azizli; Esmira Hajiyeva Gargari; Abdul Haris Muchtar; Abdurrohman Sahal (Mabadi Iqtishad Al Islami, 2025)
This study critically reassesses Islamic economic law within the rapidly expanding digital economy, emphasizing the necessity of a globally coherent Sharia-compliant regulatory architecture. Using a qualitative library research method, the paper draws from classical jurisprudence, contemporary fintech literature, and international Sharia standards to examine the tensions emerging from technological innovations such as artificial intelligence, blockchain, digital assets, and Islamic fintech platforms. Findings reveal significant regulatory fragmentation across Muslim jurisdictions, inconsistencies in Sharia interpretation, and gaps in digital literacy, which collectively hinder harmonized governance. Moreover, emerging digital financial instruments raise pressing ethical concerns related to transparency, algorithmic bias, cybersecurity, and compliance with prohibitions against riba, gharar, and maysir. The study argues that Maqasid al-Shariah—particularly the principles of ḥifẓ al-māl, maslahah, and harm prevention—provides a holistic framework for balancing innovation with ethical integrity. It also identifies the urgent need for cross-border regulatory harmonization, AI ethics protocols, enhanced Sharia governance structures, and tailored regulatory sandboxes for Islamic fintech. Ultimately, the research offers a conceptual foundation for constructing a future-ready, inclusive, and ethically resilient global Islamic digital finance system.